Impact of the Mental Status of Mother on Foetal Health – An Ayurvedic Point of View - Dayana, H. (Current Aspects in Pharmaceutical Research and Development Vol. 6, 2021)
The science of Ayurveda always suggests a holistic way of living. It strongly states that the mental status of the mother has a strong influence on foetal health. This does not start from the time of conception. Instead from the time of development of the ovum itself all the mental conditions of the mother start affecting the foetal health. In this busy urban life mental health of the mother is given less importance. Most of the women, including pregnant ladies, are under stress in the present scenario. Ayurveda very clearly explains the impact of maternal mental health on the foetus. It also suggests different consequences of its negligence and measures for maintaining the mental health of a woman during puberty, pregnancy, parturition and postnatal period. Recent studies also suggest that the thoughts and feelings of the mother will be communicated to the foetus through hormones. It can even alter the gene expression in the developing embryo. Awareness regarding the impact of the mental status of the mother on the fetus may help society to prevent the ill effects of maternal stress on the fetus. Along with the importance of nutrition and physical health care, awareness needs to be generated in society regarding the importance of maternal mental health care. This may help to reduce genetic disorders and mental health issues in the future generations.